Fiscal Federalism in Europe : Is it a Necessary Precondition for a Successful European Economic and Monetary Integration? - Berthold, Norbert (Washington, D.C. : International Monetary Fund, 1994)
An important question in the process of European integration concerns the best institutional level for stabilization policies. The theory of fiscal federalism gives criteria for evaluating if fiscal stabilization policies should take place on a centralized or on a decentralized level. This paper firstly discusses the usefulness of such policies. It reaches the conclusion that fiscal stabilization polices are in general not the adequate way of responding to shocks. However, since fiscal stabilization policies appear to be unavoidable for political reasons, the paper secondly discusses on which institutional level such policies should be located. Decentralized fiscal stabilization policies are preferable because they are disciplined more by market forces.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet